Effect of enrichment of CO2 and nitrogen fertilizer on growth of olive - Al-juboory, Ausama Y. S.; Al-djaili, Jabber A.; Al-juhishy, Mohammed S. (Journal of Kerbala for Agricultural Sciences, 2013)
An experiment was conducted in the Lath House of the Department of Horticulture/ Collage of Agriculture/ University of Baghdad. During fourteen month from 1/4/2009 to 1/7/2010, to investigate the effect of co2 enrichment and nitrogen fertilizer on growth of two cultivars of olive (Olea europaea L.) Nabali & Khoudiri. Three concentrations of CO2 (400, 800, 1200) µmol/mol and two concentrations of urea fertilizer (17, 34) gm urea/pot. Were used. The results were analyzed by genstat program. The results were summarized as followed, The treatment 1200µmol/mol CO2 was superior than other treatments in the shoot length which gave 52.56cm, while treatment 400 µmol/mol CO2 was superior than other treatments in the number of stomata which gave 133.01 stomata/mm2. The cultivar khoudeiri was superior in the number of stomata which gave 120.28 stomata/mm2. The treatment (Nabali +17g urea/pot+1200 µmol/mol CO2) was superior than other treatments which gave the highest shoot length of 60.2cm. while the treatment (Nabali +17g urea/pot+800 µmol/mol CO2) gave the highest leaf area of 1202cm2 . The treatment (khoudeiri +17g urea/pot+800 µmol/mol CO2) gave the highest number of leaf of 322.02leaf/plant, while the treatment (khoudeiri +34g urea/pot+400 µmol/mol CO2) gave the highest number of stomata in the leaf of 150.89 stomata/mm2.